Development and evaluation of a monoxide-based flexible skin dosimeter for radiotherapy at photon energies. (28th July 2021) - Yang, S.W.; Han, M.J.; Park, S.K.; Chung, J.B.; Kang, J.K.; Yu, T.S.; Rah, J.E.; Kim, J.K.; Lee, M.W.; Kim, J.Y.
Abstract: Radiation therapy uses high-energy radiation that can cause various side effects depending on the patient's exposure. In particular, the radiation exposure of the skin to reach the target volume produces side effects. Therefore, side effects as skin damage can be reduced during clinical trials using various skin dosimeters such as films and glass detectors to determine the skin dose exposure. However, accurately measuring the doses using these dosimeters is challenging due to human body curvature. In this study, a flexible skin dosimeter was developed using the photoconductor materials mercury oxide (HgO) and lead oxide (PbO). The performance of the proposed dosimeter was evaluated by measuring reproducibility, linearity, dose rate independence according to dose, and percent depth dose (PDD) at photon energy beam. The results showed that the flexible skin dosimeter using HgO material has high applicability as a skin dosimeter due to its stability compared to PbO. The results also provided useful insights for the radiation therapy field, particularly in areas where radiation measurement is difficult, depending on the human curvature. The proposed apparatus could serve in various radiation detection areas as a flexible, functional material.